Civil Effectiveness of Ecclesiastical Decisions: The Case of Religion Teachers - Celador Angón, Óscar (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2025)
The purpose of this paper is to study the civil legal effectiveness of the decisions of the ecclesiastical authorities in the context of the hiring of religion teachers by the educational administrations, as well as to analyze to what extent the state courts can exercise control over such decisions. To this end, it examines how the «missio canonica» has been regulated in cooperation agreements with religious organizations, as well as the role played by ecclesiastical decisions in the employment relationship of teachers of religion, and the scope and content of the right to internal autonomy of religious organizations in this context. The article also analyzes the main decisions of the Constitutional Court, the European Court of Human Rights and the Inter-American Court of Human Rights in this area.